Accelerated Bone Loss in Older Men: Effects on Bone Microarchitecture and Strength. (12th June 2018) - Cauley, Jane A; Burghardt, Andrew J; Harrison, Stephanie L; Cawthon, Peggy M; Schwartz, Ann V; Connor, Elizabeth Barrett; Ensrud, Kristine E; Langsetmo, Lisa; Majumdar, Sharmila; Orwoll, Eric
ABSTRACT: Accelerated bone loss (ABL) shown on routine dual‐energy X‐ray absorptiometry (DXA) may be accompanied by microarchitectural changes, increased cortical porosity, and lower bone strength. To test this hypothesis, we performed a cross‐sectional study and used high‐resolution peripheral quantitative computed tomography (HR‐pQCT) scans (Scanco Medical AG, Brüttisellen, Switzerland) to measure estimated bone strength and microarchitecture in the distal radius and distal and diaphyseal tibia. We studied 1628 men who attended the year 14 exam of the Osteoporotic Fractures in Men (MrOS) study. We retrospectively characterized areal bone mineral density (aBMD) change from the year 7 to year 14 exam in three categories: "accelerated" loss, ≥10% loss at either the total hip or femoral neck ( n  = 299, 18.4%); "expected" loss, <10% ( n  = 1061, 65.2%), and "maintained" BMD, ≥0% ( n  = 268, 16.5%). The ABL cut‐off was a safety alert established for MrOS. We used regression models to calculate adjusted mean HR‐pQCT parameters in men with ABL, expected loss, or maintained BMD. Men who experienced ABL were older and had a lower body mass index and aBMD and experienced greater weight loss compared with other men. Total volumetric BMD and trabecular and cortical volumetric BMD were lower in men with ABL compared with the expected or maintained group. Men with ABL had significantly lower trabecular bone volume fraction (BV/TV), fewer trabeculae, and greater trabecular separation at both the distal radius and tibia than men with expected loss or who maintained aBMD, all p trend <0.001. Men with ABL had lower cortical thickness and lower estimated bone strength, but there was no difference in cortical porosity except at the tibia diaphyseal site. In summary, men with ABL have lower estimated bone strength, poorer trabecular microarchitecture, and thinner cortices than men without ABL but have similar cortical porosity. These impairments may lead to an increased risk of fracture. © 2018 American Society for Bone and Mineral Research.